2017
DOI: 10.1101/198135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control of Thiol-Maleimide Reaction Kinetics in PEG Hydrogel Networks

Abstract: Michael-type addition reactions are widely used to polymerize biocompatible hydrogels. The thiol-maleimide modality achieves the highest macromer coupling efficiency of the reported Michael-type pairs, but the resulting hydrogel networks are heterogeneous, because polymerization is faster than the individual components can be manually mixed. The reactivity of the thiol dictates the overall reaction speed, which can be slowed in organic solvents and acidic buffers. Since these modifications also reduce the bioc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…3). The need for these tissue-specific hydrogels is of particular importance to instruct cells that do not produce their own matrix, for example oligodendrocytes and schwann cells 58 , and it has been shown many times that these cues can impact cell differentiation 58,59 and viability 39 . Similarly, specific ECM cues provided by integrin-binding sites 8,28,60 , inflammatory molecules 12,61 , and mechanical properties 40 , have been shown to influence the deposition of ECM proteins by astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3). The need for these tissue-specific hydrogels is of particular importance to instruct cells that do not produce their own matrix, for example oligodendrocytes and schwann cells 58 , and it has been shown many times that these cues can impact cell differentiation 58,59 and viability 39 . Similarly, specific ECM cues provided by integrin-binding sites 8,28,60 , inflammatory molecules 12,61 , and mechanical properties 40 , have been shown to influence the deposition of ECM proteins by astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that this reaction speed can be tuned by manipulating the ionic strength of the buffer, the pH, and the electronegativity of the amino acids flanking the MMP-degradable peptides. 39 Since brain cell phenotype is sensitive to the modulus of the ECM [40][41][42][43] , we needed to account for this in our design of an in vitro brain ECM. Unfortunately, we quickly discovered that reported values for Young's moduli of the brain ranged from 100s of Pa to 10s of kPa, and vary considerably among experimental techniques.…”
Section: Design Of a Synthetic Brain Ecm Hydrogelmentioning
confidence: 99%
See 1 more Smart Citation
“…Maleimide groups have higher affinity towards thiol groups, which confer shorter gelation times at physiological pH relative to hydrogels fabricated using acrylate groups 53 . Michael-type addition has been previously used to form biologically active and cytocompatible hydrogels 54,55 .…”
Section: Fabrication and Characterisation Of Full-length Fn Hydrogelsmentioning
confidence: 99%
“…However, in vivo, cell movement is largely in 3D, with cells surrounded by ECM and other cells. To test the effectiveness of the AD model in describing this type of confined cell movement, we used another PEG-based gel [39][40][41] and measured cell motility in 3D as we exposed them to different pro-migratory chemical stimulations (conditioned medium from patient cell cultures). The gels were crosslinked with MMP-sensitive peptides, but the mesh size was orders of magnitude smaller than a cell (~20-25nm).…”
Section: Cell Migration In Confined 3d Environments Is Largely Subdimentioning
confidence: 99%